Effect of thermal and non‐thermal pasteurisation on the microbial inactivation and phenolic degradation in fruit juice: a mini‐review. (14th February 2013) - Chen, Yougui; Yu, Li Juan; Rupasinghe, HP Vasantha
Abstract Fruit juice has been traditionally preserved by thermal pasteurisation. However, the applied heat can cause detrimental effects on health‐promoting components such as phenolic compounds. Several non‐thermal technologies such as membrane filtration, pulsed electric field (PEF) and ultraviolet (UV) exposure are promising methods developed for liquid food preservation. In particular, the combination of UV and PEF has proven to be more effective for microbial inactivation and maintaining nutritional quality of fruit juice compared with individual applications. © 2012 Society of Chemical Industry